Monte Carlo Dose Calculation Of Rhizophora Spp. Soy Protein Phantom At Radiotherapy Energy Range - Rabaiee, Nor Ain (2018)
The Malaysian mangrove hardwood, Rhizophora spp. has been extensively studied as a potential tissue equivalent material. However, the untreated Rhizophora spp. wood is unsuitable to be used as a phantom, due to its physical properties. Thus, the treated Rhizophora spp. particleboard was suggested as an alternative. The aim of this study was to explore the Rhizophora spp. particleboard with soy protein adhesive, as a potential phantom material, with its application validated using the Monte Carlo (MC) method at the radiotherapy energy range.